Accounting Challenges in Modern Business Environment - Saud, Naresh Singh (KVM Research Journal, 2025)
Accounting plays a critical role in modern business by providing accurate financial information necessary for decision-making, performance evaluation, and regulatory compliance. However, businesses today face numerous challenges in maintaining precise and transparent accounting records. Major challenges include complex regulatory frameworks, rapid technological changes, globalization, fraud and ethical concerns, and the increasing demand for real-time financial reporting. These challenges can affect the reliability of financial statements, stakeholder confidence, and overall organizational performance. This study explores the key accounting challenges faced by modern businesses, analyzes their causes and implications, and highlights strategies to overcome them. Findings emphasize the importance of adopting advanced accounting technologies, ensuring continuous professional development, implementing robust internal controls, and maintaining ethical standards to achieve accurate, efficient, and transparent financial reporting in a dynamic business environment.